Molecular interaction between plants and Trichoderma species against soil-borne plant pathogens - Dutta, Pranab; Mahanta, Madhusmita; Singh, Soibam Basanta; Thakuria, Dwipendra; Deb, Lipa; Kumari, Arti; Upamanya, Gunadhya K.; Boruah, Sarodee; Dey, Utpal; Mishra, A. K.; Vanlaltani, Lydia; VijayReddy, Dumpapenchala; et al. (Frontiers in Plant Science, 2023)
Trichoderma spp. (Hypocreales) are used worldwide as a lucrative biocontrol agent. Interaction of Trichoderma spp. with host plant and pathogen at molecular level is important in understanding various mechanisms adopted by the fungus to attain a friend’s status with their plant host with superior antifungal/ antimicrobial activity. Mycoparasitism, antibiosis, competition and induction of systemic acquired resistance (SAR) like response in synchrony is considered as the key factor deciding biocontrol potential of Trichoderma. Sucrose rich root exudates of host plant attracts Trichoderma. Soluble secretome of Trichoderma plays a significant role in attachment, penetration and colonization of plant roots as well as modulates mycoparasitic and antibiosis activity of Trichoderma. This review aims to gather information related to Trichoderma interaction with plant and its role as a biocontrol agents of soil borne phytopathogens and to give a comprehensive idea on diverse molecular aspects of their interaction.